2006
DOI: 10.1038/sj.jp.7211593
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and morbidity and mortality in extremely low birth weight infants

Abstract: Objective: The purpose of this study was to determine the association between hyperglycemia and mortality and late-onset infections (>72 h) in extremely low birth weight (ELBW) infants.Study design: Retrospective analysis of a prospective cohort study of 201 ELBW infants who survived greater than 3 days after birth. Mean morning glucose levels were categorized as normoglycemia (<120 mg/dl), mildmoderate hyperglycemia (120 to 179 mg/dl) and severe hyperglycemia (X180 mg/dl). Hyperglycemia was further divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
112
1
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(126 citation statements)
references
References 28 publications
6
112
1
4
Order By: Relevance
“…A laboratory study manipulating insulin and glucose independently showed that the observed benefits of intensive insulin therapy required maintenance of normoglycemia. 15 Both studies in this issue of Journal of Perinatology 4,5 found a strong association between hyperglycemia and low gestational age, whereas the association between hyperglycemia and low birth weight was either less strong 4 or not significant. 5 Kao et al 4 found a significant association between their primary outcome variable, that is, a composite outcome of either mortality or late-onset culture-proven infection (odds ratio (OR) 5.07, 95% confidence interval (CI) 1.06 to 24.3) and early (the first 3 days) severe hyperglycemia (defined as mean morning glucose equal to or greater than 180 mg/dl) after adjusting for gestational age.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…A laboratory study manipulating insulin and glucose independently showed that the observed benefits of intensive insulin therapy required maintenance of normoglycemia. 15 Both studies in this issue of Journal of Perinatology 4,5 found a strong association between hyperglycemia and low gestational age, whereas the association between hyperglycemia and low birth weight was either less strong 4 or not significant. 5 Kao et al 4 found a significant association between their primary outcome variable, that is, a composite outcome of either mortality or late-onset culture-proven infection (odds ratio (OR) 5.07, 95% confidence interval (CI) 1.06 to 24.3) and early (the first 3 days) severe hyperglycemia (defined as mean morning glucose equal to or greater than 180 mg/dl) after adjusting for gestational age.…”
mentioning
confidence: 94%
“…15 Both studies in this issue of Journal of Perinatology 4,5 found a strong association between hyperglycemia and low gestational age, whereas the association between hyperglycemia and low birth weight was either less strong 4 or not significant. 5 Kao et al 4 found a significant association between their primary outcome variable, that is, a composite outcome of either mortality or late-onset culture-proven infection (odds ratio (OR) 5.07, 95% confidence interval (CI) 1.06 to 24.3) and early (the first 3 days) severe hyperglycemia (defined as mean morning glucose equal to or greater than 180 mg/dl) after adjusting for gestational age. They also found an association of hyperglycemia (both severe early and persistent) with NEC stage II/III (OR 9.49, 95% CI 1.52 to 59.3) after adjusting for age and male gender, and an association of mortality with early (OR 15.7, 95% CI 3.74 to 65.9) or persistent (OR 30.4, 95% CI 3.37 to 274) severe hyperglycemia.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…23 We have recently reported that persistent severe hyperglycemia (serum glucose>180 mg per 100 ml) in the first days after birth is associated with a higher risk of death and sepsis among ELBW infants. 24 Most of the infants completed the full 7-day study intervention and appeared to tolerate the SWGD reasonably well, although the intervention was transiently interrupted in about 80% of them. It is rather common among ELBW infants to have residuals or lack of tolerance when enteral feedings are begun.…”
Section: Discussionmentioning
confidence: 89%